Confirmation and Identification of Salmonella spp., Cronobacter spp., and Other Gram-Negative Organisms by the Bruker MALDI Biotyper Method: Collaborative Study, First Action 2017.09. (23rd November 2019) - Bastin, Benjamin; Bird, Patrick; Benzinger, M Joseph; Crowley, Erin; Agin, James; Goins, David; Sohier, Daniele; Timke, Markus; Shi, Gongyi; Kostrzewa, Markus
Abstract: The Bruker MALDI Biotyper ® method utilizes matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF) MS for the rapid and accurate identification and confirmation of Gram-negative bacteria from select media types. The alternative method was evaluated using nonselective and selective agars to identify Cronobacter spp., Salmonella spp., and select Gram-negative bacteria. Results obtained by the Bruker MALDI Biotyper were compared to the traditional biochemical methods as prescribed in the appropriate reference methods. Two collaborative studies were organized, one in the United States focusing on Cronobacter spp. and other Gram-negative bacteria, and one in Europe focusing on Salmonella spp. and other Gram-negative bacteria. Fourteen collaborators from seven laboratories located within the United States participated in the first collaborative study for Cronobacter spp. Fifteen collaborators from 15 service laboratories located within Europe participated in the second collaborative study for Salmonella spp. For each target organism (either Salmonella spp. or Cronobacter spp.), a total of 24 blind-coded isolates were evaluated. In each set of 24 organisms, there were 16 inclusivity organisms ( Cronobacter spp. or Salmonella spp.) and 8 exclusivity organisms (closely related non- Cronobacter spp. and non- Salmonella spp. Gram-negative organisms). After testing was completed, the total percentage of correct identifications from each agar type for each strain was determined at a percentage of 100.0% to the genus level for the Cronobacter study and a percentage of 100.0% to the genus level for the Salmonella study. For both non- Cronobacter and non- Salmonella organisms, a percentage of 100.0% was correctly identified. The results indicated that the alternative method produced equivalent results when compared to the confirmatory procedures specified by each reference method.